Nox1/PAK1 is required for angiotensin II-induced vascular inflammation and abdominal aortic aneurysm formation - Hui He; Tianyu Jiang; Meng Ding; Yuan Zhu; Xiaoting Xu; Yashuang Huang; Wenfeng Yu; Hailong Ou (Redox Biology)
NADPH oxidase 1 (Nox1) is a major isoform of Nox in vascular smooth muscle cells (VSMCs). VSMC activation and extracellular matrix (ECM) remodelling induce abdominal aortic aneurysm (AAA). In this study, we aim to determine the role of Nox1 in the progression of AAA and explore the underling mechanism. ApoE−/−Nox1SMCko mice in which the Nox1 gene was smooth muscle cell (SMC)-specifically deleted in ApoE−/− background, were infused with angiotensin II (Ang II) for 28 days. We found the Nox1 deficiency reduced AAA formation and increased survival compared with ApoE−/−Nox1y/flox mice. Abdominal aortic ROS and monocyts/macrophages were reduced in the ApoE−/−Nox1SMCko mice after Ang II-infusion. The SMC-specific Nox1 deletion caused less elastin fragments and lower matrix metalloproteinase (MMP) activities in the abdominal aorta. Further, we found the Nox1 protein interacted with p21-activated kinase 1 (PAK1) in Ang II-stimulated VSMCs. The PAK1, controlled by Nox1/ROS, promoted VSMC proliferation, migration and differentiation; this is associated with increased activities of vimentin and cofilin, and cytoskeleton modulation. Moreover, we found that the Nox1/PAK1 activated the downstream MAPKs (ERK1/2, p38 and JNKs) and NF-κB, and upregulated Sp1-mediated MMP2 expression upon Ang II-stimulation. Finally, overexpression of PAK1 in the ApoE−/−Nox1SMCko mice increased vascular elastic fibre degradation, pro-inflammatory cytokine expression and AAA incidence. Therefore, we conclude that Nox1, together with PAK1, facilitates Ang II-induced VSMC activation, vascular inflammation and ECM remodelling, and thus potentiates the AAA formation.